Effectiveness of antiviral treatment in preventing death in severe hospitalised influenza cases over six seasons. Issue 7 (2nd April 2018) - Domínguez, A.; Romero-Tamarit, A.; Soldevila, N.; Godoy, P.; Jané, M.; Martínez, A.; Torner, N.; Caylà, J.A.; Rius, C.; ,
Abstract: We investigated the predictors of neuraminidase inhibitor (NAI) treatment in severe hospitalised influenza cases and the association between antiviral treatment and mortality. An observational epidemiological study was carried out in Catalonia (Spain) during 2010–2016 in patients aged ⩾18 years. Severe hospitalised cases of laboratory-confirmed influenza requiring hospitalisation were included. We collected demographic, virological and clinical characteristics. Mixed-effects logistic regression was used to estimate crude and adjusted odds ratio (aOR). We included 1727 hospitalised patients, of whom 1577 (91.3%) received NAI. Receiving NAI ⩽48 h after onset of clinical symptoms (aOR 0.37, 95% confidence interval (CI) 0.22–0.63), ⩽3 days (aOR 0.49, 95% CI 0.30–0.79) and ⩽5 days (aOR 0.50, 95% CI 0.32–0.79) was associated with a reduction in deaths. In patients admitted to the intensive care unit (ICU) (595; 34.5%), treatment ⩽48 h (aOR 0.32, 95% CI 0.14–0.74), ⩽3 days (aOR 0.44, 95% CI 0.20–0.97) and ⩽5 days (aOR 0.45, 95% CI 0.22–0.96) was associated with a reduction in deaths. Receiving treatment >5 days after onset of clinical symptoms was not associated with the reduction in deaths in hospitalised patients or those admitted to the ICU. NAI treatment of hospitalised patients with severe confirmed influenza was effective in avoiding death, mainly when administered ⩽48 h after symptom onset, but also when no more than 5 days had elapsed.